A computational method for convex optimal control problems involving linear hereditary systems - TEO, K. L.; WU, Z. S.; CLEMENTS, D. J. (International journal of systems science, 1981)
We consider a class of convex optimal control problems involving a linear hereditary system. The main aim of the paper is to devise a computational algorithm for generating a minimizing sequence of controls such that the sequence converges to the optimal control in both the weak* topology of L∞ and the almost-everywhere topology.